Aproximações preliminares entre diplomática contemporânea, paleografia e grafoscopia - GONÇALVES, Ívella de Paula Sousa (2023)
The forgery of documents is an illicit practice that promotes the development of research aimed at identifying fraud. The diplomatic develops as a discipline that analyzes the document both internally or externally and adds scientifically through methods of analysis to the identification of the authenticity of an archival document. Writing as one of the elements studied by Diplomatic becomes an object of in-depth study through methods of reading the written record understanding relevant information contained in the document. Furthermore, Graphoscopy aims to recognize the specific traces of writing that has been changed, and contributes to the field of criminology, to investigate possible crimes of altered document authenticity. It can be observed, therefore, that the use of illicit information has stimulated studies aimed at recognizing whether archival documents are authentic documents or not. Thus, we intend to describe the methods of analysis that correspond to authentic documents, based on concepts and aspects of Contemporary Diplomatics, paleography and graphoscopy. Finally, an approximation of the concepts of diplomatic, paleography, and graphoscopy through by a bibliographic search of the terms used and finally, it was proposed to expand the studies on the approximations among the disciplines in the area of Archival Science.